Exponential type orbitals with generalized hyperbolic cosine functions for atomic systems - Erturk, M. (Computer physics communications, 2015)
Radial basis functions, constructed from Slater type rn∗−1e−ζr and generalized exponential type rn∗−1e−ζrμ functions with the generalized hyperbolic cosine type functions coshpq(βr) and coshpq(βrμ), where p and q are arbitrary parameters, are proposed and applied to Hartree–Fock–Roothaan calculations of atomic systems. The performance of new basis functions within the minimal basis sets framework has been compared to numerical Hartree–Fock results and previous results presented by similar basis functions in the literature. The results obtained by the new basis sets surpass the accuracy of existing basis sets of similar hyperbolic cosine type functions.